Pituitary cells in man during aging: an immunohistological and morphometric study - Čukuranović Kokoris, Jovana; Kundalić, Braca; Pavlović, Miljana; Ugrenović, Slađana (Journal of Medical Biochemistry, 2024)
Background:  Aging is a multifactorial process, which inevitably leads to numerous changes in the life of each individual. As the lifespan of people around the world has increased, scientists began to study the mechanisms that would enable high quality and safe aging. The aim of the investigation was to indicate the changes in the cells of the pituitary gland caused by the aging process.Methods: In order to write this review, we undertook an electronic literature search through the PubMed and Google Scholar databases with the terms aging, histological, ultrastructure of pituitary cells, using also  the "related articles" option, as well as an additional analysis of authored and co-authored articles, which were necessary for this type of publication.Results: This review article describes the immunohistological, ultrastructural and morphometric characteristics of adrenocorticotropic (ACTH), somatotropic (GH), gonadotropic (LH) and folliculostellate (FS) pituitary cells during aging, in young (about 47 years) and old (over 70 years) cadavers.Conclusions: The described immunohistological and morphometric characteristics of the pituitary cells in this review indicated a significant increase in the volume density of ACTH, GH and LH cells in old cadavers, which suggested an attempt of these cells to bring the pituitary gland to a relatively balanced state.
Keywords: ACTH cells, GH cells, LH cells, FS cells, aging